Comparative typing of Pseudomonas aeruginosa by random amplification of polymorphic DNA or pulsed-field gel electrophoresis of DNA macrorestriction fragments. - Renders, N (1996)
Eighty-seven strains of Pseudomonas aeruginosa were typed by random amplification of polymorphic DNA (RAPD) and pulsed-field gel electrophoresis (PFGE) of macrorestriction fragments. Stains were clustered on the basis of interpretative criteria as presented previously for the PFGE analysis. Clusters of strains were also defined on the basis of epidemiological data and subsequently reanalyzed by RAPD. It was found that in an RAPD assay employing the enterobacterial repetitive intergenic consensus sequence ERIC2 as a primer, single band differences can be ignored; in this case, clonally related strains could be grouped as effectively and reliably as with PFGE. These data could be corroborated by the use of other primer species. However, some primers either showed reduced resolution or, in contrast, identified DNA polymorphisms beyond epidemiologically and PFGE-defined limits. Apparently, different primers define different windows of genetic variation. It is suggested that criteria for interpretation of the ERIC2 PCR fingerprints can be simple and straightforward: when single band differences are ignored, RAPD-determined grouping of P. aeruginosa is congruent with that obtained by PFGE. Consequently, this implies that RAPD can be used with trust as a first screen in epidemiological characterization of P. aeruginosa. The ability to measure the rate of molecular evolution of the P. aeruginosa genome clearly depends on the choice of restriction enzyme or primer when RAPD or PFGE, respectively, is applied for the detection of DNA polymorphisms.